From therapeutic to elective cesarean deliveries: factors associated with the increase in cesarean deliveries in Chiapas - María Graciela Freyermuth; José Alberto Muños; María del Pilar Ochoa (BMC, 2017)
Abstract Background Cesarean deliveries have increased over the past decade in Mexico, including those states with high percentages of indigenous language speakers, e.g., Chiapas. However, the factors contributing to this trend and whether they affect indigenous languages populations remain unknown. Thus, this work aims to identify some of the factors controlling the prevalence of cesarean sections (C-sections) in Chiapas between the 2011-2014 period. Methods We analyzed certified birth data, compiled by the Subsystem of Information on Births of the Secretary of Health and the National Institute of Statistics and Geography, and information regarding the Human Development Index (HDI), assembled by the United Nations Development Program. A descriptive analysis of the variables and a multilevel logistics regression model were employed to assess the role of the different factors in the observed trends. Results The results show that the factors contributing to the increased risk of C-sections are (i) women residing in municipalities with indigenous population and municipalities with high HDIs, (ii) advanced schooling, (iii) frequent prenatal checkups, and (iv) deliveries occurring in private health clinics. Furthermore, C-sections might also be associated with prolonged hospital stays. Conclusions The increasing frequency of C-sections among indigenous populations in Chiapas seems to be related to public policies aimed at reducing maternal mortality in Mexico. Therefore, public health policy needs to be revisited to ensure that reproductive rights are being respected.